2020
DOI: 10.1038/s41531-019-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in long-term Parkinson’s disease patients: a multicentre retrospective study

Abstract: While several studies have investigated the clinical progression of cognitive decline in Parkinson's disease (PD) patients, there has been a paucity of data on specifically evaluating PD patients with a disease duration of over 20 years. This study retrospectively investigated the frequency of dementia in PD (PDD) patients with a disease duration of over 20 years assessed in research clinics across the UK and Australia. Data from 2327 PD patients meeting the United Kingdom Parkinson's Disease Society Brain Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…However, both motor and cognitive function are impaired even in the early stages of PD due to dopaminergic neuronal loss in the basal ganglia ( San Martín Valenzuela et al, 2020 ). Consistent with previous studies, the PD groups in our study performed consistently poorer on cognitive and motor assessments than did the HC group ( Opara et al, 2017 ; Szeto et al, 2020 ). The early onset of cognitive deficits exacerbates gait impairments in PD because attention and executive function are indispensable for maintaining gait performance, which includes bilateral coordination and dynamic posture ( Ehgoetz Martens et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, both motor and cognitive function are impaired even in the early stages of PD due to dopaminergic neuronal loss in the basal ganglia ( San Martín Valenzuela et al, 2020 ). Consistent with previous studies, the PD groups in our study performed consistently poorer on cognitive and motor assessments than did the HC group ( Opara et al, 2017 ; Szeto et al, 2020 ). The early onset of cognitive deficits exacerbates gait impairments in PD because attention and executive function are indispensable for maintaining gait performance, which includes bilateral coordination and dynamic posture ( Ehgoetz Martens et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Patients with DLB comprise 0 to 30.5% of the cases of elderly individuals with dementia in clinical studies [5], while PDD is reported to comprise 3.6-30% [6][7][8], with estimates of over 80% in PD patients [9]. The DLB prevalence among various population-based studies ranged from 0 to 26% of all dementia cases, consistent with a population-based prevalence (approximately 10%) in rural island town in east Asia [10,11].…”
Section: Introductionmentioning
confidence: 52%
“…However, age is also related to the duration of the disease, and for that reason, it is difficult to unravel the effects of each one on the risk of dementia. Furthermore, a very recent cross-sectional study assessing dementia in long-term PD patients did not find any significant differences between age, age at onset, or disease duration between PD patients with and without dementia (83).…”
Section: Discussionmentioning
confidence: 79%